Opportunities to implement Software Defined Radio in network sensors - Sastoque-Caro, Miguel Ángel; Puerto-Leguizamón, Gustavo Adolfo; Suárez-Fajardo, Carlos Arturo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper reviews the concepts and characteristics of Software Defined Radio (SDR), focusing on the problematics of the wireless sensor networks in their fields of application; this with the purpose of finding opportunities to implement SDR functionalities to solve the requirements within the environment of a wireless sensor network.